BEHAVIOR OF THE VULVA HYGIENE IN ADOLESCENT GIRLS TO EVENTS FLUOR ALBUS - Milna Milna Puspitasari; Neni Nuraeni; Hani Handayani (Journal of Maternity Care and Reproductive Health, 2021)
Reproductive health problems in women one of them albus fluorine. Fluorine albus or leukorrhea is the discharge of fluid other than blood from the vaginal canal outside the habit of either smelling or not, and accompanied by local itching. This is due to changes in the pH in the vaginal area, the presence of viruses, also due to the behavior of the hygiene vulva is not good as well as in adolescents. The purpose of the study to determine the behavior of vulva hygiene of young women with the occurrence of Flour Albus based on the literature review with search articles through search engines google scholar obtained 10 articles that fit the criteria of inclusion and exclusion. The stages that are used begin with problem identification, screening, assessment of the quality, analyze data with IMRaD and lastly compile a data analysis report.The results found that the behavior of vulva hygiene had something to do with the incidence of flour albus. Vulva hygiene behavior that causes vaginal discharge is poor behavior in maintaining the cleanliness of the genital organs. The conclusion that bad behavior of the vulva will cause the occurrence of whiteness. It is recommended for adolescents to always pay attention to the cleanliness of genetal organs and perform good vulva hygiene to avoid fluorine albus.